Uterine cervical adenosquamous carcinoma with micropapillary components - Kenji Yorita; Koki Hirano; Takaaki Maeda (Elsevier, 2023)
A 52-year-old Japanese woman was admitted to our hospital for uterine cervical cancer treatment. She had noticed irregular genital bleeding, and uterine cervical biopsy confirmed the presence of a squamous cell carcinoma (SqCC). Radical hysterectomy, bilateral salpingo-oophorectomy, and pelvic lymph node dissection were performed, and pathology confirmed adenosquamous carcinoma (ASC) at stage pT1b1pN1cM0 and stage IIIB. Interestingly, the adenocarcinoma components, which were approximately 5% of the ASC, were purely invasive micropapillary carcinoma (IMC) or IMC-like nests. The IMC and IMC-like components were seen at the invasive front connected to the squamous component. The patient underwent cisplatin-based concurrent chemoradiotherapy and has been disease-free for 1 year following the surgery. IMC is a histopathological type of adenocarcinoma of various organs, and uterine cervical IMCs have recently attracted attention as aggressive tumors. However, uterine cervical IMCs are rare and are not an independent entity in the latest 2020 World Health Organization's classification of uterine cervical cancers. This case report describes the clinicopathological features of a patient with rare uterine cervical ASC and the curative potential of human epidermal growth factor receptor 2-targeting therapy.